The study of the varieties and lines of winter durum wheat in competitive variety-testing - A. S. Kameneva; N. E. Samofalova; N. P. Ilichkina; O. A. Dubinina; O. A. Kostylenko; V. B. Khronyuk (Зерновое хозяйство России, 2018)
The study of the varieties and lines of winter durum wheat in competitive variety-testing The article presents the study results of 15 varieties and lines of winter durum wheat in the competitive variety-testing of 2016-2017 in the main economic-valuable properties and traits. All studied samples belong to low-height forms (81-90 sm). The standard variety “Donchanka” has 3.9 points in resistance to lodging. The varieties “Yubilyarka”, “Agat Donskoy”, “Teya”, “Yakhont” and the lines “993/12”, “840/11”, “840/12” have more than 4.5 points of resistance. On average the assessment of plant wintering ranges from 3.7 to 4.5 points. The varieties “Amazonka”, “Kristella”, “Oniks”, “Diona” and the line “840/12” have the maximum mark of 4.5 points. Frost tolerance of the variety “Donchanka” has been taken as 100%. The following varieties could preserve on 2.9-24.4% more alive plants during wintering than the standard variety: “Amazonka” (+24.4%), “Oniks” (+18.4%), “Diona” (+16.8%), “Lazurit” (+9.5%), “Teya” (+5.9%), “Yantarina” (+4.8%), “Agat Donskoy” (+2.9%). The lowest frost resistance has been shown by the lines “840/11” (83.2%), “840/12” (52.5%) and “993/12” (79.9%). On average the productivity ranged from 7.40 to 8.89 t/ha during the years of study. The productivity of the lines “840/12” (8.42 т/га), “993/12” (8.74 т/га), the varieties “Kristella” (8.62 т/га), “Lazurit” (8.76 т/га), “Yantarina” (8.89 т/га) had more than one ton of increase. All studied varieties and lines have high indexes of nature weight, vitreousness and protein content in grain. There have been determined positive correlations of productivity with plant height and nature weight of winter durum wheat grain (correlation coefficient of 0.65 and 0.59 respectively).